The properties of sustainable fired clay bricks incorporating eggshell and recycled glass waste / Ahmad Humaidi Abu Hanifah, Natasha Ahmad Nawawi and Maryam Mohammad - Abu Hanifah, Ahmad Humaidi; Ahmad Nawawi, Natasha; Mohammad, Maryam (Penerbit UiTM (UiTM Press), 2025)
Fired clay bricks have been integral to construction for centuries, valued for their inherent strength and durability. However, the substantial energy demands and greenhouse gas emissions from the high-temperature brick firing process pose pressing environmental concerns. The scarcity of quality clay deposits for brickmaking has also raised fears of resource depletion. Eggshells, comprised of nearly 95% calcium carbonate, undergo a chemical transformation during firing that enhances compressive strength and reduces porosity in bricks. A recent study showed that using eggshell waste to replace clay in brick is positive. Meanwhile, soda lime silica, produced by recycling waste glass, forms a protective glaze-like coating on brick surfaces, lowering required firing temperatures and improving thermal insulation. Different eggshell powder concrete bricks were developed by replacing 0%,5%, and 10% in the clay and soda lime silica mixture to find the best composition of the brick with the desired properties. The enhanced performance of these bricks can be attributed to the inclusion of eggshells in the clay and soda lime silica mixture. As a result, the green approach conserves natural resources while meeting sustainability goals, charting a new course for environmentally responsible brick manufacturing. The findings highlight the potential of utilising eggshells to enhance the properties of clay bricks to improve their characteristic and mitigate waste reduction associated with the egg industry. The study suggests that incorporating eggshell waste into burned clay bricks improves properties and offers a sustainable approach to waste management.